2010
DOI: 10.1159/000314279
|View full text |Cite
|
Sign up to set email alerts
|

The <i>Ph1</i> Locus from Wheat Controls Meiotic Chromosome Pairing in Autotetraploid Rye (<i>Secale cereale</i> L.)

Abstract: The Ph1 locus on chromosome 5B enforces strictly bivalent pairing in polyploid wheat, but the exact mechanism of its action remains unknown. Pairing restriction involves not only wheat homoeologues and all alien introgressions but also differentiated homologues. In this study we show that chromosome 5B with its Ph1 locus also controls chromosome pairing in autotetraploid rye by apparently restricting chiasma formation between dissimilar homologues. Unlike in wheat, the effect appears to be dosage-dependent, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
1
24
1
Order By: Relevance
“…There is some indication, for instance, that Ph1, the main locus responsible for the cytological diploidization of wheat (Riley and Chapman, 1958;Griffiths et al, 2006;Greer et al, 2012, and references therein), affects recombination between dissimilar homologs (Lukaszewski and Kopecký, 2010, and references therein), suggesting that this locus regulates some basic mechanism of chromosome recognition (Greer et al, 2012). Whether the same holds true for PrBn and B. napus is an avenue worth exploring.…”
Section: Variation In Class I Co Numbers Between B Napus Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some indication, for instance, that Ph1, the main locus responsible for the cytological diploidization of wheat (Riley and Chapman, 1958;Griffiths et al, 2006;Greer et al, 2012, and references therein), affects recombination between dissimilar homologs (Lukaszewski and Kopecký, 2010, and references therein), suggesting that this locus regulates some basic mechanism of chromosome recognition (Greer et al, 2012). Whether the same holds true for PrBn and B. napus is an avenue worth exploring.…”
Section: Variation In Class I Co Numbers Between B Napus Varietiesmentioning
confidence: 99%
“…As a consequence, most allopolyploid species have inherited or evolved recombination-modifying loci that suppress CO formation between the "homoeologous chromosomes" inherited from the different parental species , and references therein). The most well characterized of these loci is Pairing homeologous1 (Ph1) from wheat (Triticum aestivum; Griffiths et al, 2006), which was shown to affect CO formation both between homoeologs (Riley and Chapman, 1958;Greer et al, 2012, and references therein) and homologs (Lukaszewski and Kopecký, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some other reports find that genome instability of arabidopsis is controlled by both genetic and environmental factors (Armstrong et al 2001). Poor homologous synapsis 1 (Phs1) and penetration and arbuscule morphogenesis 1 (Pam1) also play an important role in genome instability (Ronceret et al 2009;Lukaszewski and Kopecky 2010;Feddermann et al 2010). As a whole, the genome instability in the early stage of polyploidization is affected by multiple factors, in order to have a further understanding, more experimental models and more experimental methods should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Both in diploid [Schlegel et al, 1991] and autotetraploid rye [Lukaszewski and Kopecky, 2010], introduction of wheat chromosome 5B or its long arm with the Ph1 locus significantly reduced the MI chromosome pairing. In tetraploid rye, the effect was dosagedependent: pairing reduction was greater with 2 doses of Ph1 than with 1, and 2 doses practically eliminated multivalents.…”
mentioning
confidence: 99%
“…In a DH of autotetraploid rye each quartet of homologues should consist of 2 pairs of perfectly identical homologues; the differences between the pairs may vary depending on the level of differentiation of homologues in the parental material. Despite earlier failures [Lukaszewski and Kopecky, 2010], attempts to produce DHs to resolve this issue continued and eventually succeeded in regenerating several tetraploid DH plants with 1 or 2 doses of wheat chromosome arm 5BLwith the Ph1 locus. Here, we report that the presence of pairs of identical chromosomes in such plants did not in any way affect the pattern of chromosome pairing, indicating that in rye the Ph1 locus does not favor identical chromosomes for pairing.…”
mentioning
confidence: 99%